Cloning and Expression of 3 Chymotrypsin-like Protease of SARS-CoV-2 in E. coli using pET28a Vector - Ly, Vu Thi Duy; Giang, Tran Thi Xuan; Trang, Ngo Thu; Thai, Dinh Nho; Nghia, Phan Tuan; Loan, Nguyen Thi Hong (VNU Journal of Science: Natural Sciences and Technology; Vol 39 No 2DO - 10.25073/2588-1140/vnunst.5509, 2023)
The 3 chymotrypsin-like protease (3CLpro) of the severe acute respiratory syndrome coronavirus type 2 (SARS-CoV-2) is one of the primary targets for the development of antiviral drug therapies as it plays a critical role in viral replication. In this study, the gene encoding for SARS-CoV-2 3CLpro (918 bp) was amplified from the cDNA of the virus by polymerase chain reaction (PCR) and cloned into the pGEM-T vector. 3CLpro was then inserted into the expression vector pET28a at the end of the 6 histidine residue encoding sequence to form a fusion protein (6xHis-3CLpro). The 6xHis-3Clpro construct was successfully expressed in E. coli. The expression of 3CLpro was highest when E. coli BL21(DE3) RIL harboring pET28a- 3CLpro vector was cultured in LB medium at 20 o C, induced by 1.0 mM Isopropyl thiogalactopyranosie (IPTG)  when cell density measured by optical density at 600 nm (OD 600 )  reached 0.7-0.8 and harvested after 24 hours of induction. The recombinant 3CLpro was purified by Ni-sepharose affinity chromatography under denaturation conditions. The purified 3CLpro showed to have a 41 kDa band on sodium dodesyl sulfate-polyacrylamide gel electrophoresis (SDS-PAGE) and Western blotting using polyclonal anti-3CLpro antibody and hydrolyzed a fluorescent specific substrate of 3CLpro after renaturation.